Lingual Cortical Mandibular Bone Depression: Frequency and Clinical-Radiological Features in a Brazilian Population - Mourão,Carlos Fernando de Almeida Barros (2013)
The aim of this study was to report the frequency and clinical-radiological features of cases of lingual cortical mandibular bone depressions (LCMBD) diagnosed in consecutive panoramic radiographs and cone-beam computed tomography (CBCT) scans from a Brazilian population. The methods included a retrospective analysis of consecutive panoramic radiographs, charts from the Oral Medicine clinic and consecutive CBCT scans. All cases diagnosed as LCMBD were selected and clinical-radiological data were retrieved from the clinical charts and by the analysis of the image exams. Twenty LCMBD cases diagnosed in 18 patients were found, including 2 from 3,000 consecutive panoramic radiographs (0.07%), 6 from 2,421 Oral Medicine patients (0.25%) and 10 from 1,684 CBCT scans (0.59%). The 18 patients had a mean age of 51.5 years and 13 were males. Two patients presented bilateral lesions. Fourteen images (70%) were classified as well-defined. Eighteen affected the posterior area of the mandible and two affected the anterior mandible. Size of the lesions was larger in younger patients. In conclusion, there seemed to be a considerable radiological heterogeneity when comparing the LCMBD cases and it seemed that the images decreased in size with the increase of patient's age.